Effect of nursing intervention based on health belief model on rehabilitation of patients with chronic schizophrenia (基于健康信念模式的护理干预对慢性精神分裂症患者康复的影响) - GENG Zaixiang (耿在香); ZHOU Pingfang (周平方); WANG Aifeng (王爱凤) (中西医结合护理)
Objective To investigate the effect of nursing intervention based on health belief model (HBM) on rehabilitation of patients with chronic schizophrenia. Methods Totally 60 patients with chronic schizophrenia were randomly divided into study group and control group. The study group adopted HBW-based nursing intervention, while the control group adopted routine nursing. Positive and negative symptom scale (PANSS), Social disability scale (SDSS) and rehabilitation status scale (MRSS) were used to compare the clinical symptoms and social function improvement of the two groups. Results After 3 and 6 months of nursing intervention, the PANSS, SDSS and MRSS scores of the study group were significantly lower than those of the control group(P＜0. 05). Conclusion Nursing intervention based on HBW can relieve the mental symptoms of patients with chronic schizophrenia and improve their social function. (目的 探讨健康信念模式(HBM)对慢性精神分裂症患者康复的影响。方法 84例慢性精神分裂症患者随机分为研究组和对照组, 各42例。对照组常规干预, 研究组在对照组基础上采用HBM进行护理干预。采用阳性和阴性症状量表(PANSS)、社会功能缺陷量表(SDSS)、康复状态量表(MRSS)评估2组患者干预前后的临床症状及社会功能改善情况。结果 干预3个月、6个月后, 2组PANSS、SDSS 、MRSS评分均降低, 且研究组评分低于对照组, 差异有统计学意义(P＜0. 05)。结论 运用HBM设计的干预方法能改善慢性精神分裂症患者的精神症状, 提高其社会功能, 促进恢复。)